Valeria Rotili, Stefania Ventra, Francesco Moschini (a cura di). (2022). Il Putto reggifestone di Raffaello. Studi, indagini, restauro. Genova: Sagep Editori (diségno, 2022)
The goal of this short review is to bring to the attention of anyone interested in the material interpretation of artworks a recent publication illustrating the results of an undeniably important research that has re-assigned the paternity of a fragment of a fresco portraying a putto to the painter Rafaello Sanzio. Although the research has produced sensational results, its true appeal lies in its methodology, involving a group of scholars and the techniques and instruments they employed. [read more]